Chronotropic incompetence can limit exercise tolerance in COPD patients with lung hyperinflation - Hulo S; Inamo J; Dehon A; Le Rouzic O; Edme JL; Neviere R (International Journal of COPD, 2016)
Sébastien Hulo,1 Jocelyn Inamo,2 Aurélie Dehon,3 Olivier Le Rouzic,4 Jean-Louis Edme,1 Remi Neviere51Université Lille, CHU Lille, EA 4483, IMPact de l’Environnement Chimique sur la Santé humaine, Lille, France; 2Département de Cardiologie – CHU Fort de France, Martinique – Faculté de Médecine – Université des Antilles, France; 3Pôle d’Anesthésie Réanimation ADRU, CHU Nîmes, Nîmes, France; 4Université Lille, CNRS, Inserm, CHU Lille, Institut Pasteur de Lille, Center for Infection and Immunity of Lille, Lille, France; 5Université Lille, Inserm, CHU Lille, Lille Inflammation Research International Center, Lille, FrancePurpose: Metabolic-chronotropic relationship is the only concept that assesses the entire chronotropic function during exercise, as it takes into account individual fitness. To better understand interrelationships between chronotropic incompetence (CI), dynamic hyperinflation (DH) and exercise limitation among Global initiative for chronic Obstructive Lung Disease (GOLD) stages of chronic obstructive pulmonary disease (COPD) disease severity, we evaluated cardiopulmonary responses to symptom-limited cycle exercise in stable patients.Patients and methods: We prospectively studied 47 COPD patients classified by GOLD stage severity. Pulmonary function tests and cardiopulmonary responses to symptom-limited incremental exercise were studied. CI was defined by regression line between percent heart rate (HR) reserve and percent oxygen uptake (V’O2) reserve, ie, chronotropic-metabolic index (CMI). DH was defined from the knot resulting from the nonlinear regressions of inspiratory capacity changes from rest to peak (dynamic inspiratory capacity (ICdyn)) with percentage of maximal HR and CMI.Results: Aerobic capacity (median interquartile ranges) peak V’O2, 24.3 (23.6; 25.2), 18.5 (15.5; 21.8), 17.5 (15.4; 19.1) mL·kg-1·min-1 and CMI worsened according to GOLD severity. The optimal knot of ICdyn was equal to −0.34 L. The multivariate logistic regression showed a strong relationship between CI (outcome) and DH (odds ratio [confidence interval 95]) 25 (3.5; 191.6). Conclusion: COPD patients with DH have a poor cardiovascular response to exercise, which may be attributed to CI.Keywords: COPD, hyperinflation, chronotropic incompetence, exercise